A simple methodology for characterization of germanium coaxial detectors by using Monte Carlo simulation and evolutionary algorithms. (November 2015) - G. Guerra, J.; G. Rubiano, J.; Winter, G.; G. Guerra, A.; Alonso, H.; Arnedo, M.A.; Tejera, A.; Gil, J.M.; Rodríguez, R.; Martel, P.; Bolivar, J.P.
Abstract: The determination in a sample of the activity concentration of a specific radionuclide by gamma spectrometry needs to know the full energy peak efficiency (FEPE) for the energy of interest. The difficulties related to the experimental calibration make it advisable to have alternative methods for FEPE determination, such as the simulation of the transport of photons in the crystal by the Monte Carlo method, which requires an accurate knowledge of the characteristics and geometry of the detector. The characterization process is mainly carried out by Canberra Industries Inc. using proprietary techniques and methodologies developed by that company. It is a costly procedure (due to shipping and to the cost of the process itself) and for some research laboratories an alternative in situ procedure can be very useful. The main goal of this paper is to find an alternative to this costly characterization process, by establishing a method for optimizing the parameters of characterizing the detector, through a computational procedure which could be reproduced at a standard research lab. This method consists in the determination of the detector geometric parameters by using Monte Carlo simulation in parallel with an optimization process, based on evolutionary algorithms, starting from a set of reference FEPEs determined experimentally or computationally. The proposed method has proven to be effective and simple to implement. It provides a set of characterization parameters which it has been successfully validated for different source-detector geometries, and also for a wide range of environmental samples and certified materials. Highlights: A computational method for characterizing an HPGe spectrometer has been developed. Detector characterized using as reference photopeak efficiencies obtained experimentally or by Monte Carlo calibration. The characterization obtained has been validated for samples with different geometries and composition. Good agreement with the certified values of references material is obtained. The method has been successfully tested for environmental samples.